HUMOR DALAM PESAN DAKWAH - Mustofa Hilmi (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2018)
Humor in dakwah has an important position. The difficult material can be accepted by mad'u easily. Beside to attract attention, humor also can be used as a tool of education for mad'u and as a tool critic to against inequality that happens in society without loss the basic character of smooth and not provocative. Using improper of humor will cause a blurring the essence and purpose dakwah. There are four ethical criteria of humor which must be considered by dai. First, humor educative is humor which has the content of educating and the mission of enlightenment. Second, critical humor is humor who stimulate dai to do analysis a number of inequality and imbalance reality of life. Third, not racist, humor not contains insult, desecration, stigmatic against someone, institution, religion, race, and class. Fourth, doesn’t contain pornographic. Humor is not exploit sensational body through talk of dirty and porn.***Humor dalam dakwah menempati posisi penting. Materi yang sulit dapat dengan mudah dicerna mad’u melalui humor. Selain untuk menarik perhatian, humor juga bisa digunakan sebagai sarana edukasi mad’u dan bahkan dapat dipakai sebagai alat kritik tajam terhadap ketimpangan yang terjadi di masyarakat dengan tanpa kehilangan karakter dasarnya yang halus serta tidak provokatif. Namun penggunaan humor yang tidak tepat akan menyebabkan kaburnya esensi dan tujuan dakwah. Terdapat empat kriteria etis humor yang harus diperhatikan dai yaitu Pertama, humor edukatif yakni humor yang memiliki kandungan pesan mendidik dan membawa misi pencerahan, Kedua, humor kritis yakni humor yang menstimulus dai untuk melakukan analisis terhadap sejumlah ketimpangan dan ketidakseimbangan realitas kehidupan, Ketiga, tidak rasis, humor tidak berisi hinaan, penodaan, dan citraan stigmatis terhadap seseorang, lembaga, agama, ras, atau golongan, Keempat, Tidak berunsur pornografi, yaitu humor yang tidak mengeksploitasi tubuh dan sensasional badaniyah melalui pembicaraan jorok dan porno.